Effect of Cacao on Stem cells: A review - Sanarya Firas Hazem Saber Al- Fakje (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Chocolate (Theobroma cacao) is a natural source of bioactive compounds, particularly flavonoids such as catechin, epicatechin, and procyanidins, which exhibit potent antioxidant, anti-inflammatory, and tissue-regenerative properties. These bioactive substances have attracted increasing attention in regenerative medicine due to their potential to influence cellular functions and promote tissue repair. Recent studies suggest that cacao-derived compounds play a significant role in regulating stem cell biology by enhancing cell survival, proliferation, differentiation, and resistance to oxidative stress. The antioxidant activity of flavonoids helps reduce reactive oxygen species (ROS), thereby protecting stem cells from cellular damage and maintaining their viability during regeneration. In addition, flavonoids may modulate various signaling pathways, including Wnt/β-catenin, PI3K/Akt, and MAPK, which are essential for stem cell self-renewal and lineage commitment. These molecular mechanisms contribute to improved regenerative capacity and tissue healing. Although current evidence demonstrates promising therapeutic potential, most findings are derived from in vitro and animal studies, indicating the need for further clinical investigations to establish safety, optimal dosage, and long-term efficacy in humans. Overall, cacao bioactive compounds represent a promising natural therapeutic agent for stem cell-based regenerative medicine and may contribute to the development of innovative strategies for tissue engineering and the treatment of degenerative diseases.